Potential of GTL-Derived Biosolids for Water Treatment: Fractionization, Leachate, and Environmental Risk Analysis - Shifa Zuhara (14150862) (2022)
This study aims to understand the potential of using biosolids produced from the world’s largest gas-to-liquid (GTL) plant for water treatment applications. The metal fractionization of the two samples: raw biosolid (BS) and the pyrolyzed biosolid-BS char (BSC) (temperature: 450 °C, heating rate: 5 °C/min, residence time: 30 min) into exchangeables (F1), reducible (F2), oxidizable (F3), and residual (F4) were carried out following the Community Bureau of Reference (BCR) procedure. Characterization showed an increased carbon content and reduced oxygen content in the biochar sample. Additionally, the presence of calcium, magnesium, and iron were detected in smaller quantities in both samples. Based on the extraction results for metals, the environmental risk analysis was determined based on RAC (Risk Assessment Code) and PERI (Potential Ecological Risk Index) indices. Furthermore, leaching studies following the TCLP (Toxicity Characteristic Leaching Procedure) were conducted. The results prove that pyrolyzing stabilizes the metals present in the raw material as BS sample had high F1 fractions, and the BS char had a greater F4 fraction. While the RAC and PERI indices show that the pyrolyzed BS has a ‘low risk’, much reduced compared to the original BS sample, this is confirmed by the leaching studies that displayed minimal leaching from the pyrolyzed sample. Overall, this study proves that the GTL biosolids can best be applied for water treatment after pyrolysis. Other Information Published in: Water License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/w14244016